2017
DOI: 10.1007/s12519-017-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of relocation and environmental cleaning on reducing the incidence of healthcare-associated infection in NICU

Abstract: The comprehensive measures of relocating the NICU to a new facility design with improved environmental cleaning practice are effective and significantly reduce the incidence of HAIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
12
0
3
Order By: Relevance
“…Several studies reported that disposable pre-soaked wipes were more effective than reusable wipes. [23,25] However, other studies suggested that disposable wipes, if not used correctly, may contribute to cross contamination of other environmental surfaces while cleaning. [42,43] Disposable wipes may contribute to transfer of bacteria and spores to other surfaces if they are used incorrectly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported that disposable pre-soaked wipes were more effective than reusable wipes. [23,25] However, other studies suggested that disposable wipes, if not used correctly, may contribute to cross contamination of other environmental surfaces while cleaning. [42,43] Disposable wipes may contribute to transfer of bacteria and spores to other surfaces if they are used incorrectly.…”
Section: Discussionmentioning
confidence: 99%
“…[42,43] Disposable wipes may contribute to transfer of bacteria and spores to other surfaces if they are used incorrectly. [44] Li, Xu [25] and Wong, Huang [23] used a wipe color coding system to categorize which disposable wipes were used on specific surfaces resulting in improved cleanliness. By categorizing wipes into specific areas of the patient environment, cross contamination may be minimized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 One study showed that comprehensive measures with environmental cleaning in a NICU environment were effective and significantly reduced the incidence rate of methicillin-resistant Staphylococcus aureus. 19 A systematic review showed some strategies were differential for certain bacteria in ICUs, and when ENC was added to standard care + AMS, there was a significant reduction in the acquisition of MDR-AB. Hence, it is necessary to deeply evaluate the most effective prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 One study showed that comprehensive measures with environmental cleaning in a NICU environment were effective and significantly reduced the incidence rate of methicillin-resistant Staphylococcus aureus. 19 …”
Section: Introductionmentioning
confidence: 99%